Detectable HIV-RNA Viral Load Among HIV-Infected Pregnant Women on Treatment in Northern Uganda - Napyo, Agnes; Tumwine, James K.; Mukunya, David; Tumuhamye, Josephine; Ojok Arach, Anna A.; Ndeezi, Grace; Waako, Paul; Tylleskär, Thorkild (International Journal of Maternal and Child Health and AIDS, 2020)
Detectable HIV viral load among HIV-infected pregnant women remains a public health threat. We aimed to determine factors associated with detectable viral load among HIV-infected pregnant women in Lira, Northern Uganda. Methods: We conducted a cross-sectional survey among 420 HIV-infected pregnant women attending Lira Regional Referral Hospital using a structured questionnaire and combined it with viral load tests from Uganda National Health Laboratories. We conducted multivariable logistic regression while adjusting for confounders to determine the factors associated with detectable viral load and we report adjusted odds ratios and proportion of women with viral load less than 50 copies/ml and above 1000 copies,respectively.
Keywords: HIV-RNA Viral Load; HIV-Infected Pregnant Women; Northern Uganda